Pengaruh Radioterapi Terhadap Parameter Hasil Pemeriksaan Darah Lengkap Pasien Karsinoma Nasofaring di Rumah Sakit Pendidikan Universitas Hasanuddin Periode 2016-2018 - imam hermansyah; Eddy Zulfikar; Aton Prasetya Sibala'; William Chandra Papendang; Ahmad Fachry Toaha; Yuyun Widaningsih (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
ABSTRACT Itroduction: Nasopharyngeal carcinoma (NPC) is one of the most common malignancies in the head and neck areas. Recently, radiotherapy remain to be the treatment of choice for NPC, especially for the loco-regional type that hasn’t extend into distant metastasis. However, radiotherapy may cause side effect on the hematopoietic system, which has made complete blood tests mandatory for NPC patient that undergo radiotherapy treatment. Unfortunately, data regarding the effect of radiotherapy on complete blood test parameter of NPC patients are still very limited in Indonesia. Therefore, this study aims to analyse the effect of radiotherapy on the hematopoietic system in NPC patient based on the leukocyte count, hemoglobin concentration, and platelet count. Method: This study was an observational analytic study with cross sectional design using medical records of NPC patients that undergo full cycle of radiotherapy at the Teaching Hospital of Hasanuddin University in 2016-2018. The collected data analysed by using Friedman method. Results: Of the 41 patients included in this study, the mean significant difference on complete blood test parameter post-radiotherapy was only found in the leukocyte count (p<0,05) compared to the hemoglobin and platelet count variable (p>0,05). Discussion: Radiation on the bone marrow will cause a depression in the number of blood cells due to the destruction of hematopoietic stem cells and progenitor which are very sensitive to radiation. Based on the level of sensitivity to radiotherapy, leukocytes are the most radiosensitive, followed by platelets then erythrocytes. Conclusion: Radiotherapy has a significant effect on the changes of leukocyte count in patients with NPC. Keywords: Complete blood test, nasopharyngeal carcinoma, radiotherapy